Socioeconomic position and markers of adiposity among female teachers in Mexico. Issue 10 (9th August 2017) - Hirko, Kelly A; Lajous, Martin; Ortiz-Panozo, Eduardo; Lopez-Ridaura, Ruy; Christine, Paul J; Lȇ-Scherban, Felice; Rice, Megan S; Barrientos-Gutierrez, Tonatiuh
Abstract : Background: Occupation is often used as an indicator of socioeconomic position (SEP) in epidemiological studies, although it is unclear whether variation in SEP within a single occupational group is associated with health outcomes, including adiposity measures. Methods: We created a multidimensional SEP index using principal component analysis based on self-reported data from 36 704 female teachers in Mexico from 2008 to 2011. Multivariable Poisson regression models with robust variance were used to evaluate cross-sectional associations of SEP and markers of adiposity, including obesity (body mass index (BMI) ≥30 kg/m 2 ), elevated waist-to-hip ratio (WHR >85) and high waist circumference (WC >88 cm). Results: The most relevant indicators of SEP in this study were internet access and private health insurance. We observed significant inverse trends in obesity, WHR and WC in relation to SEP (all ptrend <0.001). Compared with women with low SEP, women in the middle (prevalence ratio (PR) 0.97, 95% CI 0.93 to 1.02) and high (PR 0.85, 95% CI 0.81 to 0.90) SEP tertiles were less likely to be obese in multivariable models. Results were similar in models of WHR and WC adjusting for BMI. For example, women with high versus low SEP were 14% less likely to have an elevated WHR (PR 0.86, 95% CI 0.83 to 0.89) and 7% less likely to have a high WC (PR 0.93, 95% CI 0.89 to 0.97). Conclusions: Our findings suggest that SEP remains relevant for adiposity within a single occupational setting and indicate that a stronger conceptualisation of SEP in epidemiological studies may be warranted.